Perceptions of Students on Project-Based Learning: Evidences from Public Schools in Pokhara - Sharma, Laxmi (Apex Journal of Business and Management, 2023)
Many initiatives introduced to enhance students learning in Nepal, and Project-Based Learning is one such. It is compulsorily integrated into the school curriculum in all subjects. Despite its timely use and integration in a school course, many arguments are raised regarding its relevance and application. This study explores the lived experiences of the students studying at the secondary level in public schools run by the Nepal government regarding their perception of Project- Based Learning in school. Seven students were interviewed in-depth, and 15 interested students in classes nine contributed reflective notes to the data collection process. The study has coined three themes by processing the data: perceptions of students on project based learning, enhancement of skills and competencies, and challenges students face in the school context of Pokhara. Findings revealed that the project-based learning introduced in school turned out to be supportive to students in shaping their learning autonomously and through real-life learning. Therefore, the research revealed a positive impact on improving classroom practices and enhancing learning among participating students. The research also finds that some students find it burdensome and loaded as many projects are assigned in a hurry. Future research might explore modes of effective interventions for helping students grow in their practices of project-based learning.